2010
DOI: 10.1007/s00423-010-0693-3
|View full text |Cite
|
Sign up to set email alerts
|

Surgical anatomy and neurophysiology of the vagus nerve (VN) for standardised intraoperative neuromonitoring (IONM) of the inferior laryngeal nerve (ILN) during thyroidectomy

Abstract: A better understanding of the variability in the VN may be useful not only to minimise complications but also to guarantee an accurate IONM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 15 publications
(39 reference statements)
3
66
1
2
Order By: Relevance
“…During CEA, the surgeon cannot find a variant VN located medial or posterior to the carotid artery. Visual identification of the recurrent laryngeal nerve (RLN) during thyroid surgery is associated with lower rates of permanent RLN palsy and is considered the gold standard by many authors [12] [13] [14]. Jatzko et al reviewed 10 reports covering 12,211 thyroid operations and found a lower rate of RLN palsy in the patients with nerve identification than in those without nerve identification (2.7% vs 7.9% for temporary palsy and 1.2% vs 5.2% for permanent palsy) [14].…”
Section: Discussionmentioning
confidence: 99%
“…During CEA, the surgeon cannot find a variant VN located medial or posterior to the carotid artery. Visual identification of the recurrent laryngeal nerve (RLN) during thyroid surgery is associated with lower rates of permanent RLN palsy and is considered the gold standard by many authors [12] [13] [14]. Jatzko et al reviewed 10 reports covering 12,211 thyroid operations and found a lower rate of RLN palsy in the patients with nerve identification than in those without nerve identification (2.7% vs 7.9% for temporary palsy and 1.2% vs 5.2% for permanent palsy) [14].…”
Section: Discussionmentioning
confidence: 99%
“…Given the varying position of the VN, the C-IONM probe must also be highly versatile. The location of the VN in relation to the common carotid artery and internal jugular vein can be classified as anterior (A), posterior (P), posterior to the internal jugular vein (PJ), or posterior to the common carotid artery (PC) (17). Most (90%) VNs lie in the posterior region of the carotid sheath in the groove between these 2 vessels.…”
Section: Stimulation Probes For C-ionmmentioning
confidence: 99%
“…Most (90%) VNs lie in the posterior region of the carotid sheath in the groove between these 2 vessels. On both sides, the most common location of the VN is the P location followed by the PC (15%) and PJ (8%) locations (17). The highly variable location of the VN is yet another reason why a simpler C-IONM probe is needed (17).…”
Section: Stimulation Probes For C-ionmmentioning
confidence: 99%
“…Additional research is warranted to confirm these results in larger groups of patients with advanced atrioventricular block. Finally, surgeon should be have perfect knowledge of the VN surgical anatomy that is the medial location of the common carotid artery (CCA) and anterolateral or lateral location of the internal jugular vein (IJV) are the most common configurations (36). Thera are few cases of medial IJV position (36).…”
Section: Safety Of C-ionm Electrodesmentioning
confidence: 99%
“…Finally, surgeon should be have perfect knowledge of the VN surgical anatomy that is the medial location of the common carotid artery (CCA) and anterolateral or lateral location of the internal jugular vein (IJV) are the most common configurations (36). Thera are few cases of medial IJV position (36). Tortuosity, kinking, or coiling of the carotid arteries are frequent with advancing age.…”
Section: Safety Of C-ionm Electrodesmentioning
confidence: 99%